Comparison of the impact of Triphala, calcium hydroxide, and chlorhexidine on root dentin microhardness - Maryam Janani; Soheila Darmiani; Bita Talebzadeh (Mashhad University of Medical Sciences, 2024)
Objective: Some endodontic procedures require using intracanal medicament between treatment sessions. The effectiveness of these agents on dentin microhardness is crucial for deciding whether to use them or not. This study aimed to compare the effectiveness of three intracanal medicaments including Triphala, calcium hydroxide (Ca(OH)2) paste, and chlorhexidine (CHX) gel on the root dentin microhardness.Methods: Forty-eight single canal mature permanent teeth were selected. Mechanical preparation was done using RaCe rotary files. The samples were randomly allocated to four equal groups (n=12), according to the applied intracanal medicament. Group 1 received no medicament, whereas the root canals in groups 2, 3, and 4 were filled with Triphala, Ca(OH)2, and CHX, respectively. Specimens were stored for one week.  Then, the roots were sectioned and the Vickers microhardness value was recorded at 0.5 mm from the pulp-dentin interface. Data were analyzed by one-way ANOVA and Tukey test and a P-value < 0.05 was considered statistically significant.Results: The mean microhardness values in the Triphala and calcium hydroxide groups were comparable to each other (P>0.05) and significantly lower compared to the control and CHX groups (P<0.05). No significant difference in microhardness was found between the CHX and control groups (P>0.05).Conclusions: Triphala and Ca(OH)2 had similar effects on root dentin microhardness. Given the favorable characteristics of Triphala medicament, it can be considered a suitable alternative to Ca(OH)2 for intracanal application.